Hieracium racemosum subsp. amideii (Asteraceae), a new hawkweed taxon from Montecristo island (Tuscan archipelago, Italy) - Gonnelli, Vincenzo; Gottschlich, Günter; Zoccola, Antonio (Phytotaxa, 2019)
A new hawkweed taxon endemic to the insula Montecristo (Tuscan archipelago, Italy), Hieracium racemosum subsp. amideii, is described and illustrated. Information on its distribution, ecology and taxonomic relationship is provided.